Dos mundos de vida juvenis às políticas públicas: percepções, sentidos e narrativas de jovens participantes do Projovem Urbano em Fortaleza. - Nascimento, Natália Ilka Morais (2013)
In a context of significant expansion in the participation of young people in youth public policies offered by various levels of government, this dissertation addresses the similarities and differences between the juvenile worlds of life and these policies. To this end, it discusses the motivations of young people to participate in the Projovem Urbano program in Fortaleza, analyzes the meanings that the interlocutors attribute to this experience and its representations about the program, emphasizing the influence of multiple experiences in the family context, in the field of affective relationships, in the processes of education, the world of work and the knowledge of their future projects. The narrators privileged in the process of dialogue in this research were five youths who participated in the program between the years 2010 and 2011, having completed it or not. The approach used was qualitative, having as methods the participant and experiential observation in activities and events of Projovem Urbano and the restoration of the social trajectories of young interlocutors through semi-structured interviews. In addition, interviews were conducted with educators and members of the program’s municipal coordination to capture official speeches and understand organizational aspects that influence the everyday of Projovem. The study indicates that the Projovem Urbano constituted itself as a significant experience in the lives of young people interviewed, having as prominent element the close relationship established between educators and students and the quality of education offered. However, there is still a gap between policies offered, effective demands of young people, the expectations generated by projects and social programs and the real possibilities of achieving these desires.